A Framework for Analyzing Operational Performance in Healthcare Industry - Singh, Bhawna; Singhi, Rushina (Indian Journal of Computer Science, 2017)
The present paper focused on designing a framework to study the impact of Big Data analytics on service supply chain management and in turn improving operational performance. Different parameters for all the three major areas have been identified to study the impact on each other. First, for Big Data Analytics, different techniques for data collection, data reposition and dataÂ analysis were identified. For Service Chain Management, there are two types of Service Supply Chains i.e. Service Only Supply Chain and Product Service Supply chain. In the healthcare industry, Service Only Chain is applicable and therefore, it was analyzed. Also, the role of data analytics in performing different steps of service chain management namely, planning, sourcing, and delivery were studied and last, the impact on operational performance was analyzed by identifying three parameters for measuring operational performance namely Turn Around Time (TAT), Order Fill Rate (OFR), and Accuracy.